Rising skill premium and the dynamics of optimal capital and labor taxation - Yi-Chan Tsai; C. C. Yang; Hsin-Jung Yu (Quantitative Economics, 2022)
With capital-skill complementarity, the secular decline in the price of capital equipment due to equipment-specific technological progress (ESTP) keeps pushing up the demand for skilled relative to unskilled labor and raising the skill premium. This paper quantitatively characterizes the dynamics of optimal taxation in response. Two main results emerge, regardless of whether the Ramsey (1927) or the Mirrlees (1971) approach is adopted. First, a tax on capital equipment corrects the 'pecuniary externalities' caused by ESTP. The correction prescribes a downward or an upward adjustment of tax rates over time, depending on whether ESTP takes place at an accelerated or a decelerated pace. Second, both Ramsey and Mirrlees approaches prescribe an increasing marginal tax rate on labor income over time. Interestingly, we find that the prescribed pattern of optimal taxation resembles the empirical decline in capital taxes and the increase in labor taxes observed in the United States. In particular, despite the significant rise in the skill premium, the welfare gains of tax reform toward optimal Ramsey taxes are modest and small.
Keywords: C61; E22; E62; H21; 330; Skill premium; optimal taxation; capital-skill complementarity; equipment-specific technological progress